2022
DOI: 10.1021/acs.analchem.2c00335
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth In Vivo Crosslinking in Minutes by a Compact, Membrane-Permeable, and Alkynyl-Enrichable Crosslinker

Abstract: Chemical crosslinking coupled with mass spectrometry (CXMS) has emerged as a powerful technique to obtain the dynamic conformations and interaction interfaces of protein complexes. Limited by the poor cell membrane permeability, chemical reactivity, and biocompatibility of crosslinkers, in vivo crosslinking to capture the dynamics of protein complexes with finer temporal resolution and higher coverage is attractive but challenging. In this work, a trifunctional crosslinker bis­(succinimidyl) with propargyl tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…The long alkyl chain provides the lipophilicity and a wider reaction radius, while the o-hydroxy group was introduced to increase its water solubility. Previous work has shown that this trifunctional cross-linker BSP can achieve in-depth in vivo crosslinking in minutes; 18 therefore, we performed a head-to-head comparison with BSP to characterize the in vivo cross-linking S5). This indicates that DSDHD has suitable membrane permeability and crosslinking reactivity, while the longer spacer arm can enhance the possible benefits of systematic analysis for protein interactions (11.4 Å of BSP vs 16.0 Å of DSDHD).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The long alkyl chain provides the lipophilicity and a wider reaction radius, while the o-hydroxy group was introduced to increase its water solubility. Previous work has shown that this trifunctional cross-linker BSP can achieve in-depth in vivo crosslinking in minutes; 18 therefore, we performed a head-to-head comparison with BSP to characterize the in vivo cross-linking S5). This indicates that DSDHD has suitable membrane permeability and crosslinking reactivity, while the longer spacer arm can enhance the possible benefits of systematic analysis for protein interactions (11.4 Å of BSP vs 16.0 Å of DSDHD).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(A) Chemical structures of the trifunctional crosslinkers with two reactive groups marked in red and an enrichable handle shaded in orange. The maximal distance restraints between the Cα atoms of the two crosslinked acidic residues were calculated by setting all intervening dihedral angles to 180° using Chem3D 19.0 software . (B) MS/MS spectra of the crosslinked peptides by the three crosslinkers.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide samples (8 mg for each) were dissolved in 4 mL of 0.1% sodium dodecyl sulfate (SDS)/PBS, and the click chemistry was carried out at 37 °C for 3 h by addition of 200 μL of 20 mM azo biotin-azide (ABA, in DMSO), 200 μL of 80 mM sodium l -ascorbate (Vc), 200 μL of 80 mM tris­(3-hydroxypropyltriazolyl-methyl) amine (THPTA), and 200 μL of 80 mM CuSO 4 in turn. After the reaction, the excess reagents Vc, THPTA, and CuSO 4 were removed using C18 tips and the excess ABA was removed using mix-mode cation exchange (MCX) columns (Waters Oasis, Ireland), as previously described . The resulting biotinylated peptides were subjected to enrichment using streptavidin agrose resin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations